The effects of production, stock and export variables on the prices of the Malaysian crude palm oil futures market / Nik Muhammad Naziman Abd Rahman and Anuar Wahab - Abd Rahman, Nik Muhammad Naziman; Wahab, Anuar (Universiti Teknologi MARA, Kedah, 2003)
Futures markets play an important role in the price discovery and forward pricing of agricultural commodities. The analysis of this study mainly focuses on the empirical test of the effects of production, stock and export variables on the prices of the Malaysian Crude Palm oil futures market. For the empirical work, correlation analysis, multiple regression and recent econometric analysis were conducted to determine the price relationships of the Malaysian Crude Palm oil futures markets with the production, stock and export variables. Order of integration for all the variables was checked using the Augmented Dickey-Fuller and Phillips-Perron tests of unit root. The Johansen approach was used to test the cointegration in a multivariate system that involved long run and short run estima.tions. The Vector Error Correction Model was used to test for causal relationships. The empirical evidence obtained from the study shows that a significant long run and short run relationships exist between the cash and future prices of the Malaysian Crude Palm oil futures market with the production, stock and export variables. The results of the causality test also shows that there is a strong relationship between the Malaysian Crude Palm oil futures market with the production, stock and export variables This means that any information flow regarding the price movement of the Malaysian Crude Palm oil futures market will affect the production, stock and export variables and vice-versa.